Repertorio Americano: A meeting point of Latin American important poets - Anchía Vindas, Alexander (2021)
The reflection will show how Joaquín García Monge could joint a group ofintellectuals and poets from different Hispano-American countries; most of them became well-known writers. When magical realism was the most important proposal in prose at the same time two generations of poets reached a proposal based on free verse as an instrument of form and a lyric expression from Hispano-America. Other authors who published in the magazine are mentioned, some examples of form of this poetry, and the Apollonian structure (i.e. metric and rhyme) as well as some examples of literary figures.